2002
DOI: 10.1023/a:1020741710060
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: To locate food, mobile consumers in aquatic habitats perceive and move towards sources of attractive chemicals. There has been much progress in understanding how consumers use chemicals to identify and locate prey despite the elusive identity of odor signals and the complex effects of turbulence on chemical dispersion. This review highlights how integrative studies on behavior, fluid physics, and chemical isolation can be fundamental in elucidating mechanisms that regulate species composition and distribution.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(23 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…In aquatic systems, studies of animal responses to chemical stimuli have focused primarily on fish and non-insect invertebrates. In the majority of these studies it has been demonstrated that the compounds involved in the prey-predator interaction were feeding stimulants, such as glycine, amino acids, sugars and organic acids [17], [18]. In the present study, a large number of non-volatile molecules found in root exudates (organic acids, amino acids, nucleosides, sugars) were tested at various concentrations, but only a few were found to induce a behavioural attraction in Coquillettidia larvae.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…In aquatic systems, studies of animal responses to chemical stimuli have focused primarily on fish and non-insect invertebrates. In the majority of these studies it has been demonstrated that the compounds involved in the prey-predator interaction were feeding stimulants, such as glycine, amino acids, sugars and organic acids [17], [18]. In the present study, a large number of non-volatile molecules found in root exudates (organic acids, amino acids, nucleosides, sugars) were tested at various concentrations, but only a few were found to induce a behavioural attraction in Coquillettidia larvae.…”
Section: Discussionmentioning
confidence: 69%
“…Therefore, the plant- Coquillettidia interaction, which is necessary to the survival of larvae (O 2 intake via plant aerenchymes for respiration [40]), was thought to be specific due to the release of VOCs-like compounds into the rhizosphere. However, despite decades of research, the identity of these aquatic VOCs-like compounds is still unclear [18]. Thus, in our first experiments we tested several molecules linked to plant secondary metabolism, but none of the flavonoids and hydroxamates (potentially present in monocotyledons) tested seemed to be involved in Coquillettidia larvae orientation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemotactic behaviors of organisms ranging in size from bacteria and plankton 39 to large mobile predators 40 are usually mediated by nutrients and other primary metabolites. 39 ' 41 Primary metabolites also mediate behavioral and physiological processes of larval settlement and metamorphosis.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrodynamic stress can influence predation rates by limiting predator mobility [19], foraging efficiency [20], chemosensory functioning [21], or in extreme cases, prevent predators from inhabiting an area [22]. In marine systems, organisms often depend upon chemical signals for foraging and predator avoidance, but the delivery and detection of chemical odor plumes is strongly influenced by hydrodynamic properties such as flow velocity and turbulence [23], [24].…”
Section: Introductionmentioning
confidence: 99%